2021
DOI: 10.1016/j.eimc.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de sero-epidemiología de la infección por SARS-CoV-2 en profesionales sanitarios de un departamento sanitario

Abstract: Objetivo: Estimar la prevalencia de anticuerpos IgG frente a SARS-CoV-2 en profesionales sanitarios (PS) de un Departamento Sanitario (DS). Métodos: Estudio de prevalencia. Se determinó la presencia de anticuerpos IgG frente a SARS-CoV-2 en los PS del DS. La determinación se realizó mediante la técnica de ELISA. El trabajo de campo se realizó del 24/04/2020 al 08/05/2020. Se recogió edad, sexo, estamento (facultativo, enfermería, etc.) y área de trabajo (atención primaria, urgencias, etc.). Se calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
3
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
3
3
2
1
Order By: Relevance
“…Similar to prior report updates, estimates did not indicate an association between sex (13 studies [ 3–6 , 9 , 11–13 , 15 , 17–20 ]) or age (12 studies [ 3–5 , 9 , 11–13 , 15 , 17–20 ]) and risk for SARS-CoV-2 infection or seropositivity. Fifteen new studies found no consistent association between health worker role (nurse vs. physician) and risk for SARS-CoV-2 infection ( 3–5 , 7–12 , 14–16 , 18–20 ).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Similar to prior report updates, estimates did not indicate an association between sex (13 studies [ 3–6 , 9 , 11–13 , 15 , 17–20 ]) or age (12 studies [ 3–5 , 9 , 11–13 , 15 , 17–20 ]) and risk for SARS-CoV-2 infection or seropositivity. Fifteen new studies found no consistent association between health worker role (nurse vs. physician) and risk for SARS-CoV-2 infection ( 3–5 , 7–12 , 14–16 , 18–20 ).…”
supporting
confidence: 54%
“…The original rapid review included 34 studies on risk factors for coronavirus infections (3 studies on SARS-CoV-2 infection, 29 studies on SARS-CoV-1 infection, and 2 studies on Middle East respiratory syndrome–CoV infection) ( 1 ); 46 studies (44 studies on SARS-CoV-2 infection, 0 studies on SARS-CoV-1 infection, and 2 studies on Middle East respiratory syndrome–CoV infection) were added in prior updates ( 2 , 21–25 ). For this update, 12 cohort studies ( 3–9 , 11 , 14 , 15 , 18 , 19 ) and 6 cross-sectional studies ( 10 , 12 , 13 , 16 , 17 , 20 ) were added ( Supplement Table 1 ). Four studies were done in the United States ( 4 , 7 , 18 , 20 ), 10 in Europe (Spain [ 5 , 11 , 14 ], Italy [ 8 , 9 ], the United Kingdom [ 12 , 17 ], France [ 13 ], Sweden [ 15 ], and the Netherlands [ 15 ]), 2 in India ( 6 , 10 ), and 1 each in China ( 19 ) and Egypt ( 3 ).…”
mentioning
confidence: 99%
“…This issue of the journal presents two seroprevalence studies carried out in Spanish hospitals after the first pandemic wave. The results vary between a prevalence of antibodies of 6.6% described by Gras-Valenti et al in a total of 4179 workers 15 from Alicante and 31% in 2590 workers from Madrid. 16 These two studies differ in the type of personnel studied (hospital and primary care personnel vs hospital), the serological parameters determined (IgG, IgM/IgA vs IgG) and the prevalence of COVID in the general population of the hospital environment, variables that could explain the differences in infection rates.…”
contrasting
confidence: 53%
“…In Barcelona, a prevalence of 11.6% and 16.4 [ 14 , 21 ] was estimated. In Alicante, in the reference health department, a rate of 6.6% was reported [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spain was one of the first European countries affected, after Italy. Community transmission and the increase in SARS-CoV-2 cases led the Spanish government to decree the confinement of the population from 14 March until 15 July 2020 [ 4 ]. Massive quarantine measures were also implemented by countries such as India, France, Italy, New Zealand, Poland, and the United Kingdom, among others.…”
Section: Introductionmentioning
confidence: 99%